Effect of immersion, submersion, and scuba diving on heart rate variability. Issue 3 (1st June 2001) - Schipke, J D; Pelzer, M
Abstract : Background —Heart rate variability (HRV) describes the cyclic variations in heart rate and offers a non-invasive tool for investigating the modulatory effects of neural mechanisms elicited by the autonomic nervous system on intrinsic heart rate. Objective —To introduce the HRV concept to healthy volunteers under control conditions and during scuba diving. In contrast with more established manoeuvres, diving probably activates both the sympathetic and parasympathetic nervous system through various stimuli—for example, through cardiac stretch receptors, respiration pattern, psychological stress, and diving reflex. A further aim of the study was to introduce a measure for determining a candidate's ability to scuba dive by providing ( a ) standard values for HRV measures (three from the time domain and three from the frequency domain) and ( b ) physiological responses to a strenuous manoeuvre such as scuba diving. Methods —Twenty five trained scuba divers were investigated while diving under pool conditions (27°C) after the effects of head out immersion and submersion on HRV had been studied. Results and conclusions —( a ) Immersion under pool conditions is a powerful stimulus for both the sympathetic and parasympathetic nervous system. ( b ) As neither the heart rate nor the HRV changed on going from immersion to submersion, the parasympathetic activation was probably due to haemodynamic alterations. ( c ) All HRV measures showed an increase in the parasympathetic activity. ( d ) If a physiological HRV is a mechanism for providing adaptability and flexibility, diving should not provoke circulatory problems in healthy subjects. ( e ) Either a lower than normal HRV under control conditions or a reduction in HRV induced by diving would be unphysiological, and a scuba diving candidate showing such characteristics should be further investigated.